Effects of Principal Leadership Effectiveness and Teacher Commitment on the Performance Level of Islamic High School Teacher in Malang City - Rahmawati, Laily Amalia; Arifin, Imron; Burhanuddin, Burhanuddin; Sunandar, Asep (Universitas Negeri Malang, 2024)
The research was aimed to examine: (1) the influence of the effectiveness of school principal leadership on teacher performance, (2) the influence of the effectiveness of school principal leadership on teacher performance, and (3) the simultaneous effects of the effectiveness of school principal leadership and teacher commitment on teacher performance in Islamic high schools across Malang City. The research employs a descriptive quantitative design utilizing a correlational approach. Data collection is conducted through questionnaires, and the collected data are analyzed using descriptive statistical techniques. Results of the study indicate (1) a significant influence of the effectiveness of school principal leadership on teacher performance; (2) a significant influence of teacher commitment on teacher performance; and (3) a significant simultaneous effects of the effectiveness of school principal leadership and teacher commitment on teacher performance. Keywords: effectiveness of principal leadership; teacher commitment; teacher performance